Generalized Formulation of 2-D Filter Structures without Global Broadcast for VLSI Implementation - Khoo, I-Hung; Reddy, Hari C.; Van, Lan-Da; Lin, Chin-Teng (My University, 2010)
A generalized formulation is developed that allows the derivation of various new 2-D VLSI filter structures, without global broadcast, using different filter sub-blocks and their interconnections (frameworks). With this formulation, lattice-type and direct-form structures realizing general 2-D IIR and FIR transfer functions, IIR transfer functions with separable denominators, and transfer functions with quadrantal magnitude symmetry are easily obtained. The separable denominator and quadrantal symmetry structures have the advantage of reduced number of multipliers.